Competences of Project Team Managers before and during the COVID - 19 pandemic - Anna MILEWSKA; Anna KACPRZAK (Communications of International Proceedings, 2021)
The article presents results of own research on identification of key competences of project team managers. This was analysed from the perspective of project team members, and prepared for the period both before and during the COVID-19 pandemic. Research was carried out in Poland, Belgium and Ukraine. They were conducted for comparison purpose. Due to the fact that project management in the time of a pandemic is a challenge for project managers, the article presents results of international research on the opinion of project managers on IT software used for project management during a pandemic. It arose from a need to introduce previously complex project activities into home office mode, which resulted in a change in the way of project implementation and management of the entire team.
Keywords: Online Gig Work; Gig Economy; Covid-19; Online Labour Index.